(untitled) (Journal of Sustainability and Environmental Management, 2023)
Traffic congestion is responsible for increased urban pollution in urban centers in developing countries. The condition of Abuja traffic congestion is no diverse. The study examines geographic analysis of traffic congestion in FCT-Abuja Nigeria. Efforts were made in this study to accomplish the objectives which are to map traffic congestion areas along selected corridors of Federal Capital Territory (FCT) Abuja using Geographical Information System (GIS) Techniques, Determine the major causes of traffic congestion in the study area and examine the solutions to traffic congestion in the study area. The study adopted random sampling techniques in the administration of well-structured 384 questionnaires to help achieve objective II and III. The data that was collected were analyzed using descriptive statistics. The descriptive analysis that was used includes means, percentage, standard deviation and structured Likert scale. The study revealed that the three major road corridors to the FCT are Abuja- keffi expressway Kubwa –Zuba express and Gwagwalada-Lokoja expressway. The study shows that too many taxis with mean score of 4.14 are the major cause of traffic congestion. While, maintenance of road is the major solution to traffic congestion in the study area with mean score of 4.19. This study recommends the provision of railway service and speedy completion of Apo-Karshi road.